Design And Fabrication Of Semi-Auto Wafer Scriber For 4-In And 8-In Wafers - Tarmizi, Illma Laili Yasmin (Universiti Sains Malaysia, 2018)
High demanding in semiconductor on wafer make fabrication of wafer keep increase years by years. Before a semiconductor device can be built, silicon must turn into a wafer which begins the growth of silicon ingot. Polysilicon crystal that formed by many small single crystals came with different orientations which required functionality which involves different steps during manufacturing. Orientation is known as line/direction when silicon wafers are slice from crystal. Die separation of thin silicon wafers and delicate substrates creates challenges for traditional saw dicing. Scribe and break die separation is an alternative to saw dicing. The feature of scribe need beneficial with thin silicon wafers which is hard and brittle material. To break the wafer, a scribe line must be created in the wafer surface where the break is desired. There are many type of diameter of wafer. This prototype is cover for 4 inch and 8 inch diameter of wafers. Design of wafer scriber being done by considering some parameter which is material, functional of every parts and machining process. Fabrication of prototype is done by considering design and machining processes. A sample of scriber is chosen for analyzing result of line scribe using scanning electron microscopy technique (SEM). The sample is analyzed by comparing width of line scribe with tip diameter of scriber. Results of scribe line does not have much different with diameter of tip and there is no crack happened on scribe line.